A bailar y contar en la fiesta [book with audioplayer] - Litwin, Eric (Litwin, Eric. Groovy Joe., 2019)
Rhyme, repetition, and Litwin's musical writing style combine with witty illustrations and math concepts in this Groovy Joe story about positivity, creativity, math, and kindness.